Design of less than 1 nm Scale Spaces on SnO2 Nanoparticles for High‐Performance Electrochemical CO2 Reduction (Adv. Funct. Mater. 8/2022). (15th February 2022) - Kim, Mun Kyoung; Lee, Hojeong; Won, Jong Ho; Sim, Woohyeong; Kang, Shin Joon; Choi, Hansaem; Sharma, Monika; Oh, Hyung‐Suk; Ringe, Stefan; Kwon, Youngkook; Jeong, Hyung Mo
Abstract : 3D Tomography In article number 2107349, Stefan Ringe, Youngkook Kwon, Hyung Mo Jeong, and co‐workers suggest a new catalytic carbon dioxide reduction reaction (CO2 RR) environment, sub‐nano scale spacing within Sn nanoparticles, which is achieved by a Li electrochemical tuning method. In this small spacing structural environment, space confinement induces enhances the activity and selectivity of CO2 RR by stabilization of rate‐limiting intermediates, resulting in effectively suppressed hydrogen evolution reaction.